Gametogenic development and spawning of the razor clam, Zenatia acinaces in northeastern New Zealand - P. E. Gribben (New Zealand Journal of Marine and Freshwater Research, 2005)
The potential exists for New Zealand to exploit already established markets for razor clams through development of fisheries or aquaculture industries for the New Zealand razor clam, Zenatia acinaces. However, fishery or aquaculture development for Z. acinaces requires an understanding of the reproductive cycle including the timing of gametogenic development and spawning. The reproductive cycle of Z. acinaces was studied over an 11‐month period from May 2000 to March 2001 at Kennedy Bay, Coromandel Peninsula, using qualitative standard histological analysis and quantitative measures of oocytes. Histological analysis indicated that Z. acinaces is dioecious and gametogenic development was synchronous between the sexes. Gametogenesis began in June with gametes maturing quickly and by August/September (late winter/ early spring) most razor clams were ripe. Spawning began as early as September (spring) although spawning mainly occurred during October. By December (summer), nearly all clams were completely spent. From January 2001 most clams could not be sexed as all residual gametes were resorbed. Razor clams remained in this stage during March 2001. Spawning began when the water temperature was around its lowest, c. 15°C. Monthly mean number of eggs/follicle was sensitive to changes in reproductive development, closely following patterns observed in the qualitative stagings. Patterns of monthly mean oocyte diameters did not adequately describe the spawning events observed in qualitative analyses. Sex ratios were equal over the size range (69–99 mm shell length) of clams that could be sexed. The data presented in this study provide valuable information on the timing of spawning events for Z. acinaces, necessary for developing sustainable management strategies and selecting broodstock for aquaculture.